Heterozygous ABCG5 Gene Deficiency and Risk of Coronary Artery Disease. (October 2020) - Nomura, Akihiro; Emdin, Connor A.; Won, Hong Hee; Peloso, Gina M.; Natarajan, Pradeep; Ardissino, Diego; Danesh, John; Schunkert, Heribert; Correa, Adolfo; Bown, Matthew J.; Samani, Nilesh J.; Erdmann, Jeanette; et al.
Abstract : Background: Familial sitosterolemia is a rare Mendelian disorder characterized by hyperabsorption and decreased biliary excretion of dietary sterols. Affected individuals typically have complete genetic deficiency—homozygous loss-of-function (LoF) variants—in the ABCG5 or ABCG8 genes and have substantially elevated plasma sitosterol and LDL (low-density lipoprotein) cholesterol (LDL-C) levels. The impact of partial genetic deficiency of ABCG5 or ABCG8 —as occurs in heterozygous carriers of LoF variants—on LDL-C and risk of coronary artery disease (CAD) has remained uncertain. Methods: We first recruited 9 sitosterolemia families, identified causative LoF variants in ABCG5 or ABCG8, and evaluated the associations of these ABCG5 or ABCG8 LoF variants with plasma phytosterols and lipid levels. We next assessed for LoF variants in ABCG5 or ABCG8 in CAD cases (n=29 321) versus controls (n=357 326). We tested the association of rare LoF variants in ABCG5 or ABCG8 with blood lipids and risk for CAD. Rare LoF variants were defined as protein-truncating variants with minor allele frequency <0.1% in ABCG5 or ABCG8 . Results: In sitosterolemia families, 7 pedigrees harbored causative LoF variants in ABCG5 and 2 pedigrees in ABCG8 . Homozygous LoF variants in either ABCG5 or ABCG8 led to marked elevations in sitosterol and LDL-C. Of those sitosterolemia families, heterozygous carriers of ABCG5 LoF variants exhibited increased sitosterol and LDL-C levels compared with noncarriers. Within large-scale CAD case-control cohorts, prevalence of rare LoF variants in ABCG5 and in ABCG8 was ≈0.1% each. ABCG5 heterozygous LoF variant carriers had significantly elevated LDL-C levels (25 mg/dL [95% CI, 14–35]; P =1.1×10 −6 ) and were at 2-fold increased risk of CAD (odds ratio, 2.06 [95% CI, 1.27–3.35]; P =0.004). By contrast, ABCG8 heterozygous LoF carrier status was not associated with increased LDL-C or risk of CAD. Conclusions: Although familial sitosterolemia is traditionally considered as a recessive disorder, we observed that heterozygous carriers of an LoF variant in ABCG5 had significantly increased sitosterol and LDL-C levels and a 2-fold increase in risk of CAD. Abstract : Supplemental Digital Content is available in the text.